2020
DOI: 10.1002/mds.28424
|View full text |Cite
|
Sign up to set email alerts
|

Soluble CD163 Changes Indicate Monocyte Association With Cognitive Deficits in Parkinson's Disease

Abstract: A BS TRACT: Background: Parkinson's disease (PD) is a neurodegenerative disorder with a significant immune component, as demonstrated by changes in immune biomarkers in patients' biofluids. However, which specific cells are responsible for those changes is unclear because most immune biomarkers can be produced by various cell types. Objectives: The aim of this study was to explore monocyte involvement in PD. Methods: We investigated the monocyte-specific biomarker sCD163, the soluble form of the receptor CD163… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
48
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 45 publications
(55 citation statements)
references
References 76 publications
6
48
1
Order By: Relevance
“…Furthermore, the iMos’ MFI of CD11b and CCR2 (females only) was higher in those patients with a MoCA scores indicative of cognitive impairment (MoCA ≤26). This corroborates that Mos with migratory capacity are associated with cognitive decline in PwP (Nissen et al, 2021; Umehara et al, 2020; Wijeyekoon et al, 2020b). Therefore, indicating that a long-term Mo dysregulation is disadvantageous for the patients, which deserves further investigation in a cohort with severe cognitive impairment.…”
Section: Discussionsupporting
confidence: 87%
See 4 more Smart Citations
“…Furthermore, the iMos’ MFI of CD11b and CCR2 (females only) was higher in those patients with a MoCA scores indicative of cognitive impairment (MoCA ≤26). This corroborates that Mos with migratory capacity are associated with cognitive decline in PwP (Nissen et al, 2021; Umehara et al, 2020; Wijeyekoon et al, 2020b). Therefore, indicating that a long-term Mo dysregulation is disadvantageous for the patients, which deserves further investigation in a cohort with severe cognitive impairment.…”
Section: Discussionsupporting
confidence: 87%
“…CD163 is a MNP specific protein whose cleavage from the membrane surface is associated with Mo activation and production of sCD163 (Moller, 2012). We have previously shown that PwP’s blood immune cells in vitro have reduced ability to downregulate CD163 expression on CD14 + Mos upon exposure to α-syn (Nissen et al, 2019); and that PwP have increased sCD163 levels in serum (females only) and in CSF (both sexes), with CSF sCD163 levels associated with α-syn and cognitive deficits (Nissen et al, 2021). This data suggested a role for CD163 + cells in PD, thus we here analyzed the CD163 expression on MNPs.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations